Field Librarianship in den USA. Bestandsaufnahme und Zukunftsperspektiven - Askey, Dale (My University, 2009)
Discusses the development and implementation of the field librarian concept in the United States. Field librarians are those that spend a significant portion of their work time outside the confines of a library, typically located within other academic buildings closer to the faculty and students they serve. The current state of this trend is analyzed, and a brief discussion of future prospects is offered. Due to the expense of offering such services on a broad scale, the scalability of the model is questioned.
Keywords: Field librarians; Subject librarians